The Host Galaxy of the Hyperactive Repeating FRB 20240114A: Behind a Galaxy Cluster - Xiang-Lei Chen; Chao-Wei Tsai; Di Li; Pei Wang; Yi Feng; Jun-Shuo Zhang; Guo-Dong Li; Yong-Kun Zhang; Lu-Lu Bao; Mai Liao; Lu-Dan Zhang; Pei Zuo; et al. (The Astrophysical Journal Letters, 2025)
We report on the optical spectroscopic observations of the host galaxy of the hyperactive repeating fast radio burst (FRB) FRB 20240114A. The host galaxy is a dwarf galaxy at a redshift of z = 0.1306 ± 0.0002. With a rest-frame coverage of 4300–7900 Å, we have detected H α , H β , [O iii ] λλ 4959,5007, [N ii ] λλ 6548,6583, and [S ii ] λ 6716 emission lines. The emission line ratios suggest that the ionization in the host galaxy is dominated by star formation. The star formation rate (SFR) derived from the H α emission line is (0.06 ± 0.01) M _⊙ yr ^−1 , and the spectral energy distribution fitting suggests the lower limit of the SFR(UV) is 0.09 M _⊙ yr ^−1 . The stellar mass is (4.0 ± 1.8) × 10 ^8 M _⊙ , making the specific SFR ${\rm{log}}\,{\rm{sSFR}}({\rm{H}}α )=-9.17± 0.07\,{{\rm{yr}}}^{-1}$ . The line ratios indicate an upper limit of a metallicity of 12 + log _10 ([O/H]) ∼ 8.5. As the nearest dwarf host galaxy with a repeating FRB, the activity of FRB 20240114A and the properties of this host galaxy closely resemble those of FRB 20121102A and FRB 20190520B. The H α -traced dispersion measure provided by the ionized gas of the host galaxy has a moderate contribution of ∼200 pc cm ^−3 , assuming a warm ionized gas. We found that the distributions of the stellar mass versus SFR are significantly different between repeating and one-off FRBs, as determined by the MANOVA test with p = 0.0116.